THE HIDDEN CHALLENGES OF LEARNING A SECOND LANGUAGE (International Congress on Economics, Management and Business Studies, 2026)
Learning a second language is a complex cognitive and social process that requires continuous practice, motivation, and appropriate learning strategies. Many students encounter hidden challenges that slow down their progress in language acquisition. These challenges include lack of confidence, time limitations, vocabulary acquisition difficulties, and age-related factors. The aim of this study is to analyze common obstacles faced by second language learners and to identify effective strategies that can improve the learning process. The research is based on the analysis of academic literature and observations of typical difficulties experienced by language learners. The findings indicate that interactive learning strategies, such as contextual vocabulary learning, multimedia resources, and time-management techniques, can significantly improve language learning outcomes. The study highlights the importance of learner-centered approaches that help students build confidence and develop practical communication skills.
Keywords: second language learning, bilingualism, vocabulary acquisition, language confidence, language education